Infratentorial and Supratentorial Strokes After a Cranioplasty. Issue 1 (January 2013) - Chitale, Rohan; Tjoumakaris, Stavropoula; Gonzalez, Fernando; Dumont, Aaron S.; Rosenwasser, Robert H.; Jabbour, Pascal
Abstract : Introduction: Complications of cranioplasty are known to include infection, wound breakdown, intracerebral hemorrhage, bone resorption, and status epilepticus. Intracerebral hemorrhagic infarction after a cranioplasty is a very rare complication with only 2 reported cases to date. We present the first case in the literature of both supratentorial and infratentorial hemorrhagic infarctions after a cranioplasty. Case Report: A 64-year-old male at an outside hospital suffered a right MCA hemorrhagic infarction requiring decompressive hemicraniectomy. One year later, the patient presents to our hospital for elective right-sided cranioplasty. The procedure was uneventful. However, postoperatively, the patient suffered a generalized tonic-clonic seizure and remained comatose. Electroencephalography showed no signs of status epilepticus, but imaging did reveal diffuse cerebral edema and both infratentorial and supratentorial hemorrhagic infarcts requiring placement of a ventriculostomy, removal of the cranioplasty plate, and suboccipital craniectomy. Postoperative tests revealed only the known right M1 occlusion, with no evidence of venous thrombosis, embolic source for new strokes, or new arterial dissection or occlusion. The patient remained with only brainstem reflexes and eventually expired. Conclusions: This is the first in the literature to report the complication of both supratentorial and infratentorial strokes after a cranioplasty procedure. Reperfusion, vessel injury, and venous stasis after cranioplasty as evaluated by multiple neurological imaging modalities are examined as possible mechanisms for this unique complication. These factors must be considered when evaluating the safety of the procedure for a patient.